1986
DOI: 10.1104/pp.80.2.403
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Control by Early Pistillate Ethylene of the Accelerated Wilting of Petunia hybrida Flowers

Abstract: Well before pollen tube penetration, ethylene has begun to disseminate from pollinated styles of Petunia hybrida flowers. Previous stigmatic application of aminoethoxyvinylglycine (AVG) completely prevented this ethylene synthesis, indicating that the endogenous 1-aminocyclopropane-1-carboxylic acid (ACC) in pollen is not readily converted on the stigma. Compared to other flower parts, the capacity of the ethylene forming enzyme was largest in the stigma. When applied to the stigma, ACC caused ethylene synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 22 publications
4
89
1
Order By: Relevance
“…It may therefore be concluded that the transported signal is not ACC but, rather, ethylene itself may be translocated or the lip may become more sensitive to ethylene following emasculation. The latter would meet our expectations as the existence of (mobile) ethylene-sensitivity factor(s) has also been suggested in cyclamen, petunia, and carnation flowers (7,9,13,19).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It may therefore be concluded that the transported signal is not ACC but, rather, ethylene itself may be translocated or the lip may become more sensitive to ethylene following emasculation. The latter would meet our expectations as the existence of (mobile) ethylene-sensitivity factor(s) has also been suggested in cyclamen, petunia, and carnation flowers (7,9,13,19).…”
Section: Discussionsupporting
confidence: 61%
“…On the contrary, they found that AVG (applied onto the stigma) was a very effective inhibitor of pollination-induced senescence even when the entire style was removed before the AVG could have reached the corolla. This made Hoekstra and Weges (9) conclude that, although direct proof was lacking, ACC may nevertheless be the transported wilting factor in Petunia. Pollination-induced corolla abscission in Digitalis was also not accompanied by an increased ethylene production in (isolated) corollas (18).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a model of auxin as the initia1 pollination signal has been proposed by Burg and Dijkman (1967) in which auxin from the pollen diffuses through the stigmaand stylar tissueof the column where it stimulates ethylene production as it moves, with the ethylene in turn directly triggering perianth senescence. Similarly, exogenous application of ACC results in a burst of ethylene production in many flowers, but this alone is not sufficient to elicit the full syndrome of postpollination development (Hoekstra and Weges, 1986) and instead leads to rapid cellular degradation throughout the flower (Zhang and ONeill, 1993). Although ethylene itself clearly plays an important role in coordinating interorgan postpollination development, ethylene alone is not sufficient to trigger initiation of ovary development and ovule differentiation in orchid flowers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that germination and growth of pollen tubes play a role in the elicitation of ethylene production by petunia styles (Hoekstra and Weges, 1986). We examined the germination and growth of pollen tubes on stigmas of stage 1 and stage 5 flowers to determine whether differences could account for the delay in pollination- induced ethylene production.…”
Section: Pollen Germination and Tube Growthmentioning
confidence: 99%
“…However, the role for pollen-held ACC in pollination-induced ethylene has been questioned. Treatment of stigmas with aminoethoxyvinylglycine, an inhibitor of ACC synthase, prevents the increase in ethylene following pollination (Hoekstra and Weges, 1986), indicating that de novo synthesis of ACC is necessary for the increase in ethylene. In addition, pollination leads to a rapid increase in ACC synthase activity in pollinated petunia styles (Pech et al, 1987).…”
mentioning
confidence: 99%